Self-emulsified oil wastewater remover and preparation method thereof
By using removers of components such as sulfomethylated tannins in the treatment of self-emulsified oil wastewater, the problems of complex oil-water separation and low pollutant removal efficiency are solved, and efficient and economical oil-water separation and pollutant removal effects are achieved.
Patent Information
- Application Number
- CN202510040759.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Self-emulsified oil wastewater treatment is difficult to effectively remove oil droplets, resulting in complex separation of oil and water. Conventional treatment methods are inefficient and costly, and may lead to hypoxia and environmental pollution in the water.
Using a self-emulsified oil wastewater remover, including sulfomethylated tannins, aluminum sulfate, polyacrylamide, sodium hydroxide and polyaluminum chloride, through emulsification destruction, charge neutralization and flocculation settlement mechanisms, Promote oil and water separation and pollutant removal.
It significantly improves the oil droplet aggregation and settlement efficiency, achieves efficient oil-water separation and pollutant removal, reduces treatment costs, and avoids hypoxia and environmental pollution in the water.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a self-emulsifying oil wastewater remover and a preparation method thereof. Background Art
[0002] The difficulty in treating self-emulsified oil wastewater lies mainly in the tiny size of the oil droplets and the stable emulsified state, which makes oil-water separation complicated. The oil droplets in self-emulsified oil wastewater usually carry a negative charge, forming a double electrical layer phenomenon that prevents the oil droplets from aggregating. At the same time, the hydrophilic solid particles also make the self-emulsified oil stably dispersed in the water, hindering the aggregation of oil droplets. These factors together make it difficult to effectively treat self-emulsified oil wastewater through conventional gravity separation, flotation and other methods.
[0003] Traditional treatment technologies, such as gravity sedimentation, centrifugal separation, filtration and chemical flocculation, often have problems such as low efficiency, high cost, complex operation or secondary pollution. For example, although the flocculation method has a simple process, good effect and strong adaptability, the standing time required after the addition of flocculants is long, and the flocs formed are easy to float, resulting in low subsequent floc separation efficiency. Although membrane separation technology has high separation efficiency, the membrane is easy to clog, has poor chemical and thermal stability, requires regular cleaning and replacement, and has high maintenance costs.
[0004] In addition, the oil droplets in the self-emulsified oil wastewater may form an oil film, which prevents oxygen from dissolving in the water, causing hypoxia in the water, death of organisms, odor, and serious environmental pollution. Therefore, the development of new and efficient self-emulsified oil wastewater treatment technology has become an urgent problem to be solved. Summary of the invention
[0005] In order to solve the problems in the background technology, the present invention provides a self-emulsifying oil wastewater remover and a preparation method thereof.
[0006] To achieve the above object, the first technical solution adopted by the present invention is: A self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 30-50 parts of sulfomethylated tannin, 15-25 parts of aluminum sulfate, 0.5-2 parts of polyacrylamide, 1-3 parts of sodium hydroxide, and 10-20 parts of polyaluminum chloride.
[0007] Preferably, the sulfomethylated tannin is obtained by sulfomethylation reaction of tannin with sodium sulfite and formaldehyde.
[0008] Preferably, the tannin is any one of bayberry tannin, chasteberry bark tannin, catechin, and tannic acid.
[0009] Preferably, it also contains 5 to 10 parts of modified active silicate.
[0010] Preferably, the modified active silicate is obtained by modifying active silicate with octyltrimethoxysilane, and has a hydrophobic layer and a long-chain alkyl group on its surface.
[0011] The second technical solution adopted by the present invention is: A method for preparing a self-emulsifying oil wastewater remover comprises the steps of uniformly mixing raw materials in a solution state, adjusting the pH value of the solution to 7.0-8.0, and then spray drying.
[0012] Preferably, the mixing temperature is 30-35°C.
[0013] Preferably, the spray drying temperature is 180-200°C at the inlet and 80-100°C at the outlet.
[0014] When the raw material contains modified active silicate, the preparation method of the modified active silicate is: mixing active silicate with an ethanol solution of octyltrimethoxysilane, reacting at pH 3-4 and 60°C for 4-5 hours, and after the reaction is completed, centrifuging to retain the solid, and washing and drying.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention applies sulfomethylated tannin to the removal of self-emulsified oil wastewater. Through the emulsification destruction effect of sulfomethylated tannin, the emulsified state of oil droplets is effectively destroyed, thereby promoting oil-water separation. The macromolecular structure and active groups of the modified tannin provide more adsorption sites and stronger bridging effect, thereby improving the speed and efficiency of oil droplet aggregation.
[0016] 2. The remover provided by the present invention also utilizes the synergistic effect of aluminum sulfate and polyaluminum chloride to strengthen the neutralization effect of negatively charged particles in wastewater, reduce the electrostatic repulsion between oil droplets, make it easier for oil droplets to aggregate into large oil droplets, thereby accelerating the sedimentation rate.
[0017] 3. The synergistic adsorption effect of the sulfomethylated tannins and modified active silicate provided by the present invention not only improves the adsorption and removal efficiency of oil droplets, but also can effectively remove organic matter and heavy metal ions in wastewater, providing a more comprehensive pollutant removal effect. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The first embodiment of the present invention provides a self-emulsifying oil wastewater remover, comprising the following raw materials in parts by weight: 30-50 parts of sulfomethylated tannin, 15-25 parts of aluminum sulfate, 0.5-2 parts of polyacrylamide, 1-3 parts of sodium hydroxide, and 10-20 parts of polyaluminum chloride.
[0020] In the process of treating self-emulsified oil wastewater, it is necessary to be able to cope with the tiny size of oil droplets and the stable emulsified state. The sulfomethylated tannin in the present invention has a strong emulsification breaking ability due to its unique molecular structure. The sulfomethylated tannin can penetrate into the surface of the oil droplets, destroy its stable emulsified state, reduce the interfacial tension of the oil droplets, thereby promoting the aggregation of the oil droplets and the oil-water separation process, laying a foundation for oil-water separation.
[0021] When the treatment agent of the embodiment of the present invention is used for self-emulsifying oil wastewater treatment, the addition of aluminum sulfate and polyaluminum chloride, two flocculants, further promotes the aggregation of oil droplets. They neutralize the negatively charged particles in the wastewater, reduce the electrostatic repulsion between the oil droplets, and make it easier for the oil droplets to aggregate into larger oil droplets through van der Waals forces and gravity. This charge neutralization effect is an indispensable part of the oil-water separation process, which greatly improves the aggregation efficiency of oil droplets.
[0022] As the oil droplets gather, polyacrylamide, as a high molecular weight polymer, has long chain molecules extending in the solution, which can capture and bind the oil droplets through adsorption and bridging, forming large flocs and settling. This flocculation and sedimentation process is the core step to achieve oil-water separation, which directly affects the treatment efficiency of the remover.
[0023] In this process, the addition of sodium hydroxide provides the best pH environment for the reaction of other components. The adjustment of pH value is crucial to the effect of flocculants, because different pH conditions will affect the charge state and molecular configuration of flocculants, thereby affecting their flocculation effect. By accurately controlling the pH value, it can be ensured that the flocculants and other components work under the best conditions, thereby improving the efficiency of the entire remover.
[0024] The treatment agent provided in the embodiment of the present invention forms a multiple action mechanism through the mutual cooperation of various raw material components, achieves synergistic effect, can comprehensively improve the wastewater treatment effect, effectively treat complex oil-water mixtures, and achieve efficient oil-water separation and pollutant removal.
[0025] In order to further improve the treatment effect, the above treatment agent may also contain 5-10 parts of modified active silicate. Modified active silicate can cooperate with polyacrylamide. Modified active silicate has higher lipophilicity and hydrophobicity due to its surface modification. It can not only adsorb oil droplets, but also enhance the structural stability of flocs through its surface activity, thereby promoting the sedimentation of flocs. Therefore, modified active silicate can promote the sedimentation of flocs formed by polyacrylamide and improve the oil-water separation efficiency.
[0026] It should be noted that the preparation method of the sulfomethylated tannin used in the present invention is a method disclosed in the prior art, that is, the sulfomethylated tannin is obtained by sulfomethylation reaction of tannin with sodium sulfite and formaldehyde.
[0027] In some preferred embodiments, the tannin is any one of bayberry tannin, wattle bark tannin, catechin, and tannic acid.
[0028] In some preferred embodiments, the modified active silicic acid is obtained by modifying active silicic acid with octyltrimethoxysilane, and has a hydrophobic layer and a long-chain alkyl group on its surface.
[0029] The second embodiment of the present invention provides a method for preparing a self-emulsifying oil wastewater remover, wherein the raw materials are uniformly mixed in a solution state, the pH of the solution is adjusted to 7.0-8.0, and then spray-dried.
[0030] There is no special limitation on the mixing order of the raw materials, and it can be adjusted by those skilled in the art according to the actual situation. The solution state refers to the solution formed after the raw materials are dissolved in deionized water. As to whether the raw materials need to be dissolved in deionized water, those skilled in the art can select a suitable method according to the characteristics of the raw materials.
[0031] In some preferred embodiments, the mixing temperature is 30-35°C.
[0032] In some preferred embodiments, the spray drying temperature is 180-200°C at the inlet and 80-100°C at the outlet.
[0033] When the raw material contains modified active silicate, the preparation method of the modified active silicate is: mixing active silicate with an ethanol solution of octyltrimethoxysilane, reacting at pH 3-4 and 60°C for 4-5 hours, and after the reaction is completed, centrifuging to retain the solid, and washing and drying.
[0034] In order to make the technical solution of the present invention clearer, the self-emulsifying oil wastewater remover and its effects are described in detail through multiple specific embodiments below.
[0035] The test equipment and preparations of the following examples are as follows: Electronic balance (Sartorius, Germany), electric blast constant temperature dryer (Shanghai Fomar Experimental Equipment), stainless steel reactor (Shanghai Laibei), electric constant temperature water bath (Jiangsu Kedao), rotary evaporator (Shanghai Darlow Scientific Instruments), pulverizer (Shandong Tianfang Machinery), magnetic stirrer (Shanghai Meiyingpu), Soxhelt extractor (Qingdao Juchuang); chemicals and reagents were purchased from Sigma-Aldrich.
[0036] Example 1 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 46 parts of sulfomethylated wattle bark tannin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, 12 parts of polyaluminum chloride, and 8 parts of modified active silicate.
[0037] Wherein, the preparation method of sulfomethylated tannin comprises: S11. dissolving the tannin powder of wattle bark in deionized water; S12. Add 37% formaldehyde solution and sodium sulfite to the tannin solution of wattle bark, and after they are completely dissolved, continue the reaction at 70-80°C for 4-6 hours; S13. After the reaction is completed, the reaction mixture is cooled to room temperature and the pH of the product is adjusted to 7-8; S14. The neutralized solution is concentrated under reduced pressure at 50-60° C. to about 1 / 3 of the original volume, and the concentrate is spray-dried or vacuum-dried to obtain sulfomethylated balsam pear bark tannin powder.
[0038] The preparation method of modified active silicate comprises: S21. Dissolve octyltrimethoxysilane in anhydrous ethanol to prepare a 5% solution, and adjust the pH of the solution to 3-4; S22. Mix the dried active silicic acid with the octyltrimethoxysilane solution and stir the mixture at 60° C. for 4 to 5 hours; S23. After the reaction is completed, the mixture is centrifuged and washed alternately with anhydrous ethanol and deionized water for 3 to 5 times to remove unreacted silane, and the washed product is vacuum dried at 60° C. for 12 h.
[0039] Preparation method of self-emulsifying oil wastewater remover, S31. The above raw materials are mixed successively in deionized water and the pH is adjusted to between 7.0 and 8.0; S32. The mixture is spray dried with the inlet temperature set at 180-200°C and the outlet temperature controlled at 80-100°C to obtain a solid powder product. The dried product is crushed and sieved using a 100-mesh sieve to ensure uniform particle size.
[0040] Example 2 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 30 parts of sulfomethylated wattle bark tannin, 15 parts of aluminum sulfate, 0.5 parts of polyacrylamide, 1 part of sodium hydroxide, 10 parts of polyaluminum chloride, and 5 parts of modified active silicate.
[0041] The preparation method of sulfomethylated wattle bark tannin, modified active silicic acid, and self-emulsifying oil wastewater remover is shown in Example 1.
[0042] Example 3 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 50 parts of sulfomethylated wattle bark tannin, 25 parts of aluminum sulfate, 2 parts of polyacrylamide, 3 parts of sodium hydroxide, 20 parts of polyaluminum chloride and 10 parts of modified active silicate.
[0043] The preparation method of sulfomethylated wattle bark tannin, modified active silicic acid, and self-emulsifying oil wastewater remover is shown in Example 1.
[0044] Example 4 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 38 parts of sulfomethylated wattle bark tannin, 23 parts of aluminum sulfate, 1 part of polyacrylamide, 2 parts of sodium hydroxide, 18 parts of polyaluminum chloride and 6 parts of modified active silicate.
[0045] The preparation method of sulfomethylated wattle bark tannin, modified active silicic acid, and self-emulsifying oil wastewater remover is shown in Example 1.
[0046] Example 5 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 46 parts of sulfomethylated bayberry tannin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, 12 parts of polyaluminum chloride, and 8 parts of modified active silicate.
[0047] The preparation method of sulfomethylated bayberry tannin, modified active silicic acid, and self-emulsifying oil wastewater remover is shown in Example 1.
[0048] Example 6 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 46 parts of sulfomethylated catechin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, 12 parts of polyaluminum chloride and 8 parts of modified active silicate.
[0049] The preparation method of sulfomethylated catechin, modified active silicic acid and self-emulsifying oil wastewater remover is shown in Example 1.
[0050] Example 7 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 46 parts of sulfomethylated tannic acid, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, 12 parts of polyaluminum chloride, and 8 parts of modified active silicate.
[0051] The preparation method of sulfomethylated tannic acid, modified active silicic acid and self-emulsifying oil wastewater remover is shown in Example 1.
[0052] Example 8 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 46 parts of sulfomethylated wattle bark tannin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide and 12 parts of polyaluminum chloride.
[0053] The preparation method of sulfomethylated wattle bark tannin and self-emulsifying oil wastewater remover is shown in Example 1.
[0054] Example 9 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 30 parts of sulfomethylated wattle bark tannin, 15 parts of aluminum sulfate, 0.5 parts of polyacrylamide, 1 part of sodium hydroxide and 10 parts of polyaluminum chloride.
[0055] The preparation method of sulfomethylated wattle bark tannin and self-emulsifying oil wastewater remover is shown in Example 1.
[0056] Example 10 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 50 parts of sulfomethylated wattle bark tannin, 25 parts of aluminum sulfate, 2 parts of polyacrylamide, 3 parts of sodium hydroxide and 20 parts of polyaluminum chloride.
[0057] The preparation method of sulfomethylated wattle bark tannin and self-emulsifying oil wastewater remover is shown in Example 1.
[0058] Embodiment 11 The self-emulsifying oil wastewater remover comprises the following raw materials in parts by weight: 38 parts of sulfomethylated wattle bark tannin, 23 parts of aluminum sulfate, 1 part of polyacrylamide, 2 parts of sodium hydroxide and 18 parts of polyaluminum chloride.
[0059] The preparation method of sulfomethylated wattle bark tannin and self-emulsifying oil wastewater remover is shown in Example 1.
[0060] Comparative Example 1 The remover, compared with Example 8, differs only in that sulfomethylated wattle bark tannin is not used, that is, it comprises the following raw materials in parts by weight: 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, and 12 parts of polyaluminum chloride.
[0061] Comparative Example 2 The remover, compared with Example 8, is different only in that the wattle bark tannin is not modified, and the sulfomethylated wattle bark tannin is replaced by an equal amount of wattle bark tannin, that is, it includes the following raw materials in parts by weight: 46 parts of unmodified wattle bark tannin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, and 12 parts of polyaluminum chloride.
[0062] Comparative Example 3 The remover, compared with Example 1, is different only in that the wattle bark tannin is not modified, and the sulfomethylated wattle bark tannin is replaced by an equal amount of wattle bark tannin, that is, it includes the following raw materials in parts by weight: 46 parts of unmodified wattle bark tannin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, 12 parts of polyaluminum chloride, and 8 parts of modified active silicic acid.
[0063] Comparative Example 4 The remover, compared with Example 1, is different only in that the active silicate is not modified, and the modified active silicate is replaced by an equal amount of active silicate, that is, it includes the following raw materials in parts by weight: 46 parts of sulfomethylated wattle bark tannin, 21 parts of aluminum sulfate, 1.8 parts of polyacrylamide, 2 parts of sodium hydroxide, 12 parts of polyaluminum chloride, and 8 parts of unmodified active silicate.
[0064] Test example The performance of the treatment agents prepared in the above examples and comparative examples was tested as follows.
[0065] 1. Preparation of simulated wastewater: Add 2% of the self-emulsifying cutting fluid to deionized water, stir for 30 minutes using a high-speed stirrer to prepare simulated wastewater, and measure the initial oil content, COD, turbidity and other indicators. Then, 10g of the treatment agent of the embodiment and the comparative example were added to the simulated wastewater, and the oil content, COD value, turbidity and other indicators of the treated water samples were measured.
[0066] 2. Determination of oil content: Under the condition of pH ≤ 2, the oil substances in the sample are extracted with tetrachloroethylene, the extract is dehydrated with anhydrous sodium sulfate, and then adsorbed with magnesium silicate to remove polar substances such as animal and plant oils, and then determined by infrared spectrophotometer.
[0067] 3. COD determination: Using the potassium dichromate method, take a certain volume of water sample and dilute it as needed. Add a certain amount of potassium dichromate standard solution, as well as an appropriate amount of mercuric sulfate and silver sulfate-sulfuric acid solution. Heat the mixed water sample to reflux for a certain period of time, usually 2 hours. After cooling, add the ferrous iron indicator and titrate with ammonium ferrous sulfate standard solution until the solution color changes to reddish brown. Calculate the COD value based on the volume of ammonium ferrous sulfate standard solution consumed in the titration.
[0068] 3. Turbidity determination: Use a scattering turbidity meter, take an appropriate amount of supernatant into a colorimetric tube, shake it gently to avoid bubbles, wipe the outer wall of the colorimetric tube, and put it into the instrument for determination.
[0069] 4. Analysis of floc characteristics (1) Zeta potential determination: Use a Zeta potential analyzer to take the flocculated sample and filter it with a 0.45 μm filter membrane. Inject the sample into the sample pool, set the measurement parameters, and record the potential value (mV).
[0070] (2) Determination of floc particle size distribution: Use a laser particle size analyzer to take the flocculated sample, dilute it appropriately, set the instrument parameters, add an appropriate amount of sample to the sample pool, start stirring, and record D 50 value.
[0071] 5. Surface tension measurement: Use a surface tension meter to take water samples before and after treatment, control the temperature to 25±0.1℃, clean the platinum ring, and measure the surface tension.
[0072] Table 1 Removal of pollutants from self-emulsified oil in Examples 1-11 and Comparative Examples 1-4 .
[0073] The removal of pollutants from the self-emulsifiable oil by the above examples and comparative examples is shown in Table 1. Example 1 (sulfomethylated tannin + modified active silicic acid) performed best in all evaluation indicators, with an oil content removal rate of 98.5%, a COD removal rate of 95.2%, and a turbidity removal rate of 99.1%, far exceeding the other examples and the control group. This result clearly proves that the synergistic effect of sulfomethylated tannin and modified active silicic acid can significantly improve the treatment effect.
[0074] By comparing the results of Example 1 with Comparative Examples 3 and 4, it can be clearly seen that the modified process significantly improves the treatment effect. Compared with Comparative Example 4 using unmodified active silicate, Example 1 improves the oil content removal rate by 7.7 percentage points (from 90.8% to 98.5%), COD removal rate by 7.3 percentage points (from 87.9% to 95.2%), and turbidity removal rate by 5.6 percentage points (from 93.5% to 99.1%). This significant performance improvement is mainly attributed to the fact that the modified active silicate enhances the structural stability of the flocs and promotes the growth and sedimentation of the flocs. This can be seen from the average floc particle size D 50 The data further confirmed that D 50 The value (178.6 μm) is much higher than that of Comparative Example 4 (142.3 μm).
[0075] At the same time, by comparing the data of Example 8 with Comparative Examples 1 and 2, it can be observed that the sulfomethylation process has an important influence on the performance of tannin. Compared with Comparative Example 2 using unmodified tannin, the oil content removal rate of Example 8 increased by 11.6 percentage points (from 84.1% to 95.7%), the COD removal rate increased by 11.1 percentage points (from 81.5% to 92.6%), and the turbidity removal rate increased by 10.6 percentage points (from 87.2% to 97.8%). This improvement is mainly reflected in the fact that the sulfomethylation process enhances the interaction between tannin molecules and the interface of oil droplets, and more effectively destroys the emulsified state of oil droplets. Zeta potential data also support this conclusion. The Zeta potential of Example 8 (-18.2mV) is significantly better than that of Comparative Example 2 (-25.3mV), indicating that the flocs formed are more stable and not easy to redisperse.
[0076] The data of surface tension reduction rate further confirmed the superiority of sulfomethylated tannins. Example 8 achieved a reduction rate of 38.2%, which was significantly higher than 28.5% of Comparative Example 2. This result is consistent with the mechanism that sulfomethylated tannins can more effectively reduce the oil-water interfacial tension. It is worth noting that other examples also showed excellent treatment effects, which highlights the universal applicability of the sulfomethylation process in improving the tannin treatment performance. In general, this set of experimental data strongly demonstrated the synergistic advantages of sulfomethylated tannins and modified active silicate in treating self-emulsified oil wastewater.
[0077] Their synergistic effect not only significantly improves the removal rate of oil, COD and turbidity, but also improves the characteristics of flocs, making them more stable and easier to settle, thereby achieving more efficient oil-water separation. This innovative formula provides an efficient and reliable new solution to the complex problem of self-emulsified oil wastewater treatment.
[0078] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-emulsifying oil wastewater remover, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of sulfomethylated tannin, 15-25 parts of aluminum sulfate, 0.5-2 parts of polyacrylamide, 1-3 parts of sodium hydroxide and 10-20 parts of polyaluminum chloride.
2. The remover according to claim 1, characterized in that The sulfomethylated tannin is obtained by sulfomethylating tannin with sodium sulfite and formaldehyde.
3. The remover according to claim 2, wherein the tannin is any one of bayberry tannin, wattle bark tannin, catechin, and tannic acid.
4. The remover according to any one of claims 1 to 3, characterized in that: It also contains 5 to 10 parts of modified active silicate.
5. The remover according to claim 4, characterized in that The modified active silicic acid is obtained by modifying active silicic acid with octyltrimethoxysilane, and has a hydrophobic layer and a long-chain alkyl group on its surface.
6. A method for preparing the self-emulsifying oil wastewater remover according to any one of claims 1 to 5, characterized in that: After the raw materials are mixed uniformly in a solution state, the solution pH is adjusted to 7.0-8.0 and then spray-dried.
7. The method according to claim 6, characterized in that The mixing temperature is 30-35°C.
8. The method according to claim 6, characterized in that The spray drying temperature is 180~200℃ at the inlet and 80~100℃ at the outlet.
9. The method according to claim 6, characterized in that When the raw material contains modified active silicate, the preparation method of the modified active silicate is: Mix active silicic acid with an ethanol solution of octyltrimethoxysilane, react at pH 3-4 and 60°C for 4-5 hours, and after the reaction is completed, centrifuge to retain the solid, wash it, and dry it.
Citation Information
Patent Citations
Production method of material for improving chemical waste water
CN107777738A
Rapid treatment method for petrochemical wastewater
CN110015774A
Method for preparing amphiphilic lignin nano material based on pulping black liquor, amphiphilic lignin nano material and oil sludge cleaning agent
CN112341634A
Intelligently-controlled environment-friendly coke oven circulating ammonia water treatment process
CN115925166A
Low-temperature efficient oil removal cleaning agent
CN116356339A